2015
DOI: 10.1080/01694243.2015.1054177
|View full text |Cite
|
Sign up to set email alerts
|

Simple method for preparing ZnO superhydrophobic surfaces with micro/nano roughness

Abstract: In this paper, a facile, inexpensive, and environment-friendly method is developed to construct a superhydrophobic surface with hierarchical micro/nanostructures on the steel substrates. The superhydrophobic surface was fabricated by magnetic agitation of a mixture of micro and nanosized Zinc oxide (ZnO) suspensions on a substrate, after being modified with a low-surface energy monolayer of stearic acid, the as-prepared coating exhibits self-cleaning properties with a water contact angle of 162°and a sliding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In the low-frequency region, the bands at 1467 and 1561 cm −1 are assigned to -COO-stretching vibrations in CH 3 (CH 2 ) 16 COO-groups, implying that the stearic acid on the surface of ANB. This finding is also consistent with the result obtained by Qing et al [42].…”
Section: Ft-ir and Xps Analysis Of Surface-coated And Uncoated Anb Posupporting
confidence: 94%
See 1 more Smart Citation
“…In the low-frequency region, the bands at 1467 and 1561 cm −1 are assigned to -COO-stretching vibrations in CH 3 (CH 2 ) 16 COO-groups, implying that the stearic acid on the surface of ANB. This finding is also consistent with the result obtained by Qing et al [42].…”
Section: Ft-ir and Xps Analysis Of Surface-coated And Uncoated Anb Posupporting
confidence: 94%
“…The asymmetric and symmetric stretching vibration of -CH 2 -groups [41] that confirms the presence of stearic acid on the surface of ANB was observed in the spectra of SA-coated ANB powders. Besides, the -COOstretching vibrations in CH 3 (CH 2 ) 16 COO-groups [42], implying that the stearic acid on the surface of ANB. FT-IR spectra of samples also indicated no chemical interaction between SA and ANB, thus proving the inertness of ANB, which only behaves as a host carrier.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al prepared a ZnO nanorod-like microstructure surface through a wet chemical route and modified it with various alkanoic acids to obtain a superhydrophobic surface [32]. Qing et al used stearic acid to modify ZnO and prepared a superhydrophobic coating on the surface of stainless steel by dip coating [33]. Sutha et al prepared ZnO nanowalls on glass substrates by sonochemical technology, and then modified them with 1H, 1H, 2H, and 2H-perfluorooctyltrichlorosilane to obtain a superhydrophobic surface [34] Wei et al prepared a flower-like ZnO structure on a foamed nickel substrate through a hydrothermal and decomposition process, and then obtained a superhydrophobic surface by hydrophobic treatment of 1H, 1H, 2H, and 2H-perfluorooctyltrichlorosilane [35].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO is largely used as an additive in rubbers, plastics, ceramics, glasses and pigments, and is one of the most relevant semiconducting material due to its optical and electrical properties [21]. Many studies are reported in the literature concerning the use of ZnO in the preparation of superhydrophobic rigid surfaces, some of which involved the chemical treatment with stearic acid (Figures S1 and S2) [22,23,24,25,26,27]. Lee et al reported on a facile approach for the fabrication of a superhydrophobicnanocoatings on different substrates (both rigid as silicon and flexible as polyethylene terephthalate (PET)) through a simple but long-lasting procedure based on the spin-coating deposition of a series of layers of ZnONPs, each subjected to a chemical modification step with stearic acid [20].…”
Section: Introductionmentioning
confidence: 99%